2011
DOI: 10.1007/s00431-011-1438-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk ghrelin, leptin, and fat levels changing foremilk to hindmilk: is that important for self-control of feeding?

Abstract: The aim of this study was to evaluate the changes in the ghrelin, leptin, and fat levels in the foremilk and hindmilk and the possible relationship between these levels with the age and growth of term healthy infants. Sixty-two babies were subdivided (according to their nutrition) into breastfed (BF), formula-fed (FF), and BF plus FF (BF + FF) groups. The total and active ghrelin and tryglyceride levels and the total cholesterol levels in the foremilk and hindmilk were studied at the first and second visits (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 43 publications
9
42
1
2
Order By: Relevance
“…The temporary drop in protein concentration was consistent with differences described by Nommsen et al [42]. Whereas some studies have reported a decrease in concentrations of leptin [75] and adiponectin [30,33,36,66] (measured predominantly in skim HM), others found the opposite trend for adiponectin [11,35], no change [76] or significant fluctuations [11,21] for leptin. More research is required to clarify these relationships.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The temporary drop in protein concentration was consistent with differences described by Nommsen et al [42]. Whereas some studies have reported a decrease in concentrations of leptin [75] and adiponectin [30,33,36,66] (measured predominantly in skim HM), others found the opposite trend for adiponectin [11,35], no change [76] or significant fluctuations [11,21] for leptin. More research is required to clarify these relationships.…”
Section: Discussionsupporting
confidence: 89%
“…In this study we confirmed no systematic change between pre- and post-feed samples for concentrations of protein, lactose and whole and skim HM leptin throughout the first 12 months of lactation (Table 3), and report for the first time that whole milk adiponectin concentrations also do not differ significantly pre- to post-feed. Care however should still be taken as fat content [77], ghrelin [75] and glucagon-like peptide 1 (GLP-1) [24] change between pre- and post-feed, further highlighting the importance of prudent sampling.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may be useful for constituents where prior work has demonstrated that fore or hind milk is an adequate representation of interest: for example, vitamin A concentrations per gram of milk fat at the population level (Stoltzfus and Underwood, 1995) and calcium (Prentice, 2000) or if the constituent of interest demonstrates minimal variation across a breastfeeding bout (such as many proteins; Neville et al 1984). However, this approach is problematic for macronutrients and many hormones, such as leptin (Daly et al, 1993b;Karatas et al, 2011).…”
Section: Milk Samplingmentioning
confidence: 99%
“…These bioactive milk peptides also play important roles, such as energy intake and systemic and local imflammatory status. [5, 15, 33]. At this point, another important focus of this study was a positive correlation between CRP and these three adipokines.…”
Section: Discussionmentioning
confidence: 95%